2019
DOI: 10.1111/jth.14336
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage with direct oral anticoagulants in patients with brain tumors

Abstract: Summary Intracranial hemorrhage (ICH) is common in patients with brain tumors. We compared rates of ICH with DOACs and low molecular weight heparin. DOACs were associated with a lower incidence of ICH in primary brain tumors. DOACs appear safe to administer to patients with brain tumors. Summary BackgroundDirect oral anticoagulants (DOACs) are efficacious in the treatment of cancer‐associated thrombosis but are associated with an increased risk of hemorrhage compared with low‐molecular‐weight heparin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 13 publications
4
69
1
3
Order By: Relevance
“…At the time, there were no data addressing the relative safety of rivaroxaban vs. LMWH in those patients. However, more recent reports support the use of a DOAC in patients with primary or metastatic cancer of the brain …”
Section: Discussionsupporting
confidence: 89%
“…At the time, there were no data addressing the relative safety of rivaroxaban vs. LMWH in those patients. However, more recent reports support the use of a DOAC in patients with primary or metastatic cancer of the brain …”
Section: Discussionsupporting
confidence: 89%
“…In patients with brain tumors and CAT, a previous study has shown that therapeutic doses of DOACs were not associated with increased risk of intracranial bleeding relative to LMWH. 18 Although both studies used Khorana score to identify high-risk patients, the included types of malignancies remained heterogeneous and could carry different thrombotic and bleeding risks. However, data from AVERT and CASSINI studies are the highest level of evidence to date regarding using DOACs as primary thromboprophylaxis for ambulatory cancer patients, and it is likely not feasible to conduct dedicated studies in each tumor type.…”
Section: Cautionsmentioning
confidence: 99%
“…In addition, patients with malignancy involving the brain are at high risks of both bleeding and thrombosis, but this population was underrepresented (24 patients in AVERT and excluded in CASSINI), and whether this high‐risk population could have similar outcomes remains unclear. In patients with brain tumors and CAT, a previous study has shown that therapeutic doses of DOACs were not associated with increased risk of intracranial bleeding relative to LMWH . Although both studies used Khorana score to identify high‐risk patients, the included types of malignancies remained heterogeneous and could carry different thrombotic and bleeding risks.…”
Section: Introductionmentioning
confidence: 99%
“…Риск развития ВТЭО у пациентов с первичным или метастатическим поражением головного мозга в 15 раз выше, чем в общей популяции онкологических пациентов [38]. Лечение и медикаментозная профилактика ВТЭО у этой категории пациентов сопряжены с высоким риском внутричерепных кровоизлияний.…”
Section: особенности профилактики втэо у пациентов с опухолями головнunclassified